DETERMINATION OF CLENBUTEROL IN MEAT SAMPLES WITH ELISA AND GC-MS METHOD - Hajrulai-Musliu, Zehra; Uzunov, Risto; Stojkovski, Velimir; Dimitrieska-Stojkovik, Elizabeta; Stojanovska-Dimzoska, Biljana; Sekulovski, Pavle (European Scientific Journal, ESJ, 2013)
It is essential from the public health point of view, that the Macedonian regulatory agencies implement a monitoring surveillance program that not only uses preliminary screening methods for the determination of clenbuterol, but also uses confirmatory methods such as MS techniques. Thus, the aim of this work was to monitor the presence of clenbuterol residues in bovine meat muscle collected from the veterinarian inspectors, using screening and confirmatory methods. From 55 bovine meat samples analyzed by the ELISA test, 1 (1.8%) of presented clenbuterol residues was 1.19 μg/kg, 7 (12.7%) from 0.5 to 1.0 μg/kg, 13 (23.64%) from 0.1 to 0.5 μg/kg and 34 (61.82%) were below the limit of detection (LOD) of 0.1 μg/kg. In this study, from twenty one meat samples analyzed by GC-MS only one sample was confirmed positive for clenbuterol. The obtained results indicated that clenbuterol was still illegally used as a bovine growth promoter.